Perlindungan Hukum Terhadap Notaris Melalui Prinsip Kehati-Hatian Sebagai Upaya Pencegahan Tindak Pidana Pencucian Uang - Aldy Valentino; M Arief Amrullah; Ermanto Fahamsyah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Financial transactions cause the emergence of legal relationships between two or more parties. In order to expedite the flow of financial transactions, it is required to produce evidence in the civil sector, therefore the participation of Notaries is required as a public official who has the task of making authentic deeds. The deed in question is an authentic deed made by or before a notary according to the form and procedures stipulated in the Law. In making authentic deeds, it is not uncommon for Notaries to meet with parties who are perpetrators of money laundering crimes with the aim of obtaining protection under the confidentiality provisions of the Notary profession. Isn't the Notary only responsible and authorized to make authentic deeds and other powers, all related to documents, then where are the suspicious transactions carried out by his clients? This problem must be studied in more depth to see how the Notary applies the principle of prudence in getting to know the presenters and the legal consequences of authentic deeds that do not apply the principle of prudence in getting to know the presenters.